Different dosages effectiveness of Ovaprim on the maturation of freshwater lobster (Cherax quadricarinatus) - Feranosa, Cinda; Komariyah, Siti; Fadlon Haser, Teuku (Universitas Malikussaleh, 2024)
Freshwater lobsters have been developed as a commodity for consumption since 2003. The need for this commodity is increasing but production is still very low, so the price of freshwater lobsters is quite high and expensive. Therefore, it is necessary to carry out reproduction to carry out the seeding process for Freshwater Lobsters (LAT) using an injection technique in the form of the Ovaprim Hormone to accelerate the maturity of the LAT gonads. This study aims to examine the administration of different doses of the ovaprim hormone on the maturation of freshwater lobster broodstock. The research was conducted for 60 days. The method used was a Randomized Block Design (RAK) with 4 treatments and 3 replications. The treatments in this study were P0 (control), P1 (0,3 ml), P2 (0,5 ml) and P3 (0,7 ml). The parameters observed in this study were Gonad Maturity Index (IKG), Egg Diameter and Pleopode Fecundity. The results of the observations showed that giving different doses of ovaprim to the maturation of freshwater crayfish was not significantly different (P<0.05) to the Gonad Maturity Index IKG), Egg Diameter and Pleopode Fecundity but was significantly different to the P0 (control) treatment. The best treatment in this study was treatment P3 (0.5 ,l) because it had the highest performance between the other treatments.Keywords: egg diameter; fecundity; freshwater lobster; maturation; ovaprim